Mechanism of Body Water Regulation in Indian Desert Donkey - Khan, M S (Annals of Arid Zone, 2016)
The body water distribution pattern in normally hydrated, 9 day wat r deprived and rehydrated donkeys of Rajasthan desert, India, were measured during late winter. The donkeys failed to maintain extracelluler fluid volume. Recovery during rehydration regime was very slow and even after 4 days of rehydration only 44% of SCN space losses were regained. Unlike ca11,1eland goat, the cell and gut water was of no help and ’the interstitial water compensates, mainly, the water losses due to dehydration